Angular distribution and asymmetries in flavor-changing neutral-current decay B → K* l⁺ l⁻ - Korchin, A.Yu.; Kovalchuk, V.A.; Lazarenko, D.O. (Вопросы атомной науки и техники, 2012)
The fully differential angular distribution for the rare flavor-changing neutral current decay Bd⁰ → K*⁰( → K⁻π⁺)e⁺e⁻ is studied. The emphasis is placed on accurate treatment of the contribution from the processes Bd⁰ → K*⁰( → K⁻π⁺)V with intermediate vector resonances V = ρ(770), ω(782), φ(1020), J/ψ, ψ(2S), … decaying into the e⁺e⁻ pair. The two versions of the vector-meson-dominance model for the transition Vγ are used and tested. The branching ratio, longitudinal polarization fraction of the K*⁰ meson, transverse asymmetry AT⁽²⁾ and forward-backward asymmetry are compared with data from BaBar and CDF, and predictions for experiments at LHCb and B factories are made. Изучено полное дифференциальное угловое распределение редкого распада Bd⁰ → K*⁰( → K⁻π⁺)e⁺e⁻, индуцированного нейтральным током, изменяющим аромат. Акцентировано внимание на аккуратном рассмотрении вкладов от процессов Bd⁰ → K*⁰( → K⁻π⁺)V с промежуточными векторными резонансами V = ρ(770), ω(782), φ(1020), J/ψ, ψ(2S),…, распадающимися на e⁺e⁻ -пару. Использованы две версии модели векторной доминантности для перехода Vγ. Относительная вероятность распада, доля продольной поляризации K*⁰ мезона, поперечная асимметрия AT⁽²⁾ и асимметрия "вперед-назад'' сравниваются с данными BaBar и CDF, а также выполнены предсказания для экспериментов LHCb и B-фабрик. Досліджено повний диференційний кутовий розподіл рідкого розпаду Bd⁰ → K*⁰( → K⁻π⁺)e⁺e⁻, індукованого нейтральним струмом, який змінює аромат. Акцентовано увагу на акуратному розгляді вкладів від процесів Bd⁰ → K*⁰( → K⁻π⁺)V з проміжними векторними резонансами V = ρ(770), ω(782), φ(1020), J/ψ, ψ(2S),…, які розпадаються на e⁺e⁻ -пару. Використані дві версії моделі векторної домінантності для переходу Vγ. Відносна ймовірність розпаду, частка повздовжньої поляризації K*⁰ мезона, поперечна асиметрія AT⁽²⁾ та асиметрія "вперед-назад'' порівнюються з даними BaBar та CDF, а також виконані передбачення для експериментів LHCb та B-фабрик.